Failure To Release Butterflies From The Cocoons Of The Silkworm (Bombyx Mori L.), As A Factor Of Reduced Yield Through Selective Selection - Abdrimova Gulbahor Erimmatovna; Oripov Otabek Oripovich; Eltaeva Aygerim Azat kizi (Periodica Journal, 2024)
The yield of silkworm cocoons depends on many factors: genetic conditioning, compliance with agricultural rules, quality of food, storage conditions of moths and cocoons, and the number of butterflies emerging from the cocoons. The productivity and income of grain farms directly depends on the number of butterflies that emerge from cocoons and lay eggs. By selective selection aimed at increasing the percentage of healthy butterflies emerging from cocoons, it is possible to significantly reduce the loss of grain due to the failure of butterflies to emerge. Purposeful work to increase the yield of butterflies led to the creation of lines of sex-marked breeds C-5, C-10, C-13, C-14 with an approximately 2-fold improvement in butterfly emergence.
Keywords: silkworm; grena; caterpillar; cocoon